2000
DOI: 10.1054/bjoc.2000.1161
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric study on malignant pleural mesothelioma and non-occupational exposure to asbestos

Abstract: Insufficient evidence exists on the risk of pleural mesothelioma from non-occupational exposure to asbestos. A population-based case–control study was carried out in six areas from Italy, Spain and Switzerland. Information was collected for 215 new histologically confirmed cases and 448 controls. A panel of industrial hygienists assessed asbestos exposure separately for occupational, domestic and environmental sources. Classification of domestic and environmental exposure was based on a complete residential hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 16 publications
4
103
0
1
Order By: Relevance
“…In general, these studies were not able to quantify the magnitude of environmental asbestos exposure, but used proxy measures such as distance to source. This study showed that the distance of the plant to the midpoint of a postal code area was associated with number of polluted sites and exposed households, but correlation coefficients between 0.36 and 0.52 indicate that spatial risk models based on proximity measures (Magnani et al, 2000;Magnani et al, 2001;Maule et al, 2007;Kurumatani and Kumagai, 2008;Musti et al, 2009) may give rise to considerable misclassification.…”
Section: External Validitymentioning
confidence: 80%
See 2 more Smart Citations
“…In general, these studies were not able to quantify the magnitude of environmental asbestos exposure, but used proxy measures such as distance to source. This study showed that the distance of the plant to the midpoint of a postal code area was associated with number of polluted sites and exposed households, but correlation coefficients between 0.36 and 0.52 indicate that spatial risk models based on proximity measures (Magnani et al, 2000;Magnani et al, 2001;Maule et al, 2007;Kurumatani and Kumagai, 2008;Musti et al, 2009) may give rise to considerable misclassification.…”
Section: External Validitymentioning
confidence: 80%
“…In contrast to other studies we could not take into account the asbestos emission from the factory during its asbestos producing period (Magnani et al, 2000(Magnani et al, , 2001Maule et al, 2007;Kurumatani and Kumagai, 2008;Musti et al, 2009). Although some information was available on the total amount of asbestos emitted by the pipe plant permitted by legal authorities in certain years, the information was too sparse.…”
Section: Restrictions In Available Informationmentioning
confidence: 95%
See 1 more Smart Citation
“…Other work had shown an increased risk of mesothelioma among residents of the LHA (Magnani et al 1995). Their method was based on one used for epidemic diseases and predicted a total number of deaths and a date for the end of the 'epidemic'.…”
Section: Predictions Of Mesothelioma From Non-occupational Exposurementioning
confidence: 99%
“…1 There is strong evidence of increased risk following occupational exposure and, to some extent, environmental exposure, usually from industrial point sources or household contact 2 and asbestos-contaminated soil. 3 The dimension of excess risk at levels of exposure encountered in urban areas is almost unknown.…”
Section: Dear Sirmentioning
confidence: 99%